2002
DOI: 10.1176/appi.ajp.159.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Citalopram, Perphenazine, and Placebo for the Acute Treatment of Psychosis and Behavioral Disturbances in Hospitalized, Demented Patients

Abstract: Citalopram was found to be more efficacious than placebo in the short-term hospital treatment of psychotic symptoms and behavioral disturbances in nondepressed, demented patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 294 publications
(180 citation statements)
references
References 29 publications
3
160
1
10
Order By: Relevance
“…Citalopram was reported to be effective in reducing all kinds of NPS in a study of 98 patients (Nyth and Gottfries, 1990). In a DB RCT study of 85 patients treated with citalopram, perphenazine or a placebo for up to 17 days, citalopram was found to be superior to a placebo in treating psychosis and behavioural symptoms (Pollock et al, 2002). Nevertheless, four other studies reported that antidepressants were not more effective than a placebo for NPS (Auchus and Bissey-Black, 1997;Teri et al, 2000;Lyketsos et al, 2003;Finkel et al, 2004), and a review concluded that antidepressants were not very effective in the treatment of NPS (Seitz et al, 2011).…”
Section: Antidepressive Medicationmentioning
confidence: 98%
“…Citalopram was reported to be effective in reducing all kinds of NPS in a study of 98 patients (Nyth and Gottfries, 1990). In a DB RCT study of 85 patients treated with citalopram, perphenazine or a placebo for up to 17 days, citalopram was found to be superior to a placebo in treating psychosis and behavioural symptoms (Pollock et al, 2002). Nevertheless, four other studies reported that antidepressants were not more effective than a placebo for NPS (Auchus and Bissey-Black, 1997;Teri et al, 2000;Lyketsos et al, 2003;Finkel et al, 2004), and a review concluded that antidepressants were not very effective in the treatment of NPS (Seitz et al, 2011).…”
Section: Antidepressive Medicationmentioning
confidence: 98%
“…16 Selective serotonin reuptake inhibitors seem to have efficacy for treatment of agitation in patients with AD. Studies have demonstrated benefits for agitation with citalopram compared with placebo 76 and similar efficacy compared with risperidone. 77 …”
Section: Tricyclic Antidepressant Agentsmentioning
confidence: 99%
“…The etiology of behavioral and psychological symptoms in dementia is not the same as in schizophrenia, and a serotonin deficit is thought to be important (Herrmann and Lanctôt, 1997). Treatment with serotonin receptor antagonists (like the atypical antipsychotics) seems irrational from that point of view, and serotonin-specific reuptake inhibitors (SSRIs) have also been shown to have a better effect on aggressive behavior than antipsychotic agents (Pollock et al, 2002). There is still a need for randomized studies comparing the efficacy of different classes of psychotropics in the treatment of behavioral disturbances (e.g.…”
Section: A N T I P S Y C H O T I C S a N T I P S Y C H O T I C S N Omentioning
confidence: 99%